Acceptance and continued use of digital libraries by postgraduate students in Malaysian intensive research universities / Abd Latif Abdul Rahman - Abdul Rahman, Abd Latif (2012)
The digital library is regarded as a new information system product in libraries and information centres around the world. It is also regarded as one of the most innovative efforts taken by library and information professionals in their attempt to enhance the library and information services for their users. Library and information professionals are capitalizing on the flexibility and advantages of the digital library to offer new and sophisticated services to their library users. Currently, users are already relying on the availability of digital libraries for their information needs to support their daily tasks. In the context of the university environment, the digital library in the university is being utilized by students and academics almost constantly. In this context, librarians and information professionals who are responsible for the development of a digital library need to understand the intricacies of it so that the advantages and benefits can be exploited to better provide library and information services. One of the most important aspects of the digital library in the university environment is its acceptance and continued use by the university community, particularly by students. The success of the digital library depends on its acceptance and continued usage by users. Therefore, it is crucial to investigate and understand not only its acceptance and continued usage, but also how and why it is being accepted and continued used. With this knowledge, better library and information services can be offered to the users at large. Samples comprised 534 respondents from four Malaysian intensive research universities and were obtained through questionnaire. This study investigated factors that are expected to influence the willingness of postgraduate students to continued use the digital library based on modified UTAUT, SOUTAUT, NUTAUT and Delone and Mclean's Information Success Model. The modified model is comprised of constructs represented by several latent variables; namely Performance Expectancy (PE), effort expectancy (EE), information quality (IQ) and digital library services (DLS), and these are moderated by age, gender and experience in using digital library. Results show that performance expectancy, effort expectancy and information quality are positively related to the Continued Use of the Digital Library, while the digital library services variable is negatively related to the Continued Use of the Digital Library. There is no evidence that age and gender have any significant interactions with the relationship between Performance Expectancy and Continued Use of the Digital Library, while experience in using a digital library and age of user significantly interacts with the relationship between Effort Expectancy and Continued Use of the Digital Library. This provides evidence of a moderating effect of experience and age in the Continued Use of the Digital Library. It is expected that this research will provide new insights into research on the acceptance and continued use the library in a digital environment.